2009
DOI: 10.1007/s10805-010-9104-1
|View full text |Cite
|
Sign up to set email alerts
|

More than Lip Service: The Development and Implementation Plan of an Ethics Decision-Making Framework for an Integrated Undergraduate Business Curriculum

Abstract: In the face of the business community's widening concern about corporate ethical behavior, business schools are reexamining how they ensure that students appreciate the ethical implications of managerial decision making and have the analytical tools necessary to confront ethical dilemmas. The current approaches adopted by colleges vary from mere 'lip service' to embedding ethics at the core of the curriculum. This paper examines the experience of several US universities that have incorporated business ethics i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…This is due in part to the fact that the gatekeepers of progress are the lecturers themselves (Ryan & Tilbury 2013) and there is a wide diversity in levels of interest and/or understanding of how to integrate CSR (Dean & Beggs 2006;McDonald 2004). For example, university teaching staff typically have a high degree of autonomy in terms of deciding course content and often assume that others will cover ethical issues (Cant & Kulik 2009). Full embeddedness of CSR across the curriculum is also hampered by the poor coverage of ethics and CSR in most business textbooks (Acevedo 2013;Baetz & Sharp 2004).…”
Section: Business Educationmentioning
confidence: 99%
“…This is due in part to the fact that the gatekeepers of progress are the lecturers themselves (Ryan & Tilbury 2013) and there is a wide diversity in levels of interest and/or understanding of how to integrate CSR (Dean & Beggs 2006;McDonald 2004). For example, university teaching staff typically have a high degree of autonomy in terms of deciding course content and often assume that others will cover ethical issues (Cant & Kulik 2009). Full embeddedness of CSR across the curriculum is also hampered by the poor coverage of ethics and CSR in most business textbooks (Acevedo 2013;Baetz & Sharp 2004).…”
Section: Business Educationmentioning
confidence: 99%
“…Currently, business schools vary on the coverage and approach to ethics education. Some business schools are giving mere "lip service" to the subject, while a small number of others have effectively integrated ethics into the core of their curriculum (Cant and Kulik 2009). Institutions have also struggled to tie business ethics programs to the overall concept of assurance of student learning and continuous improvement.…”
Section: Discussionmentioning
confidence: 99%
“…First, while some studies have focused on describing approaches and experiences of business schools that have integrating ethics into the curriculum (Bishop 1992;Cant and Kulik 2009), our study goes a step further. We provide a conceptual model for developing an interdisciplinary ethics program that combines critical success factors, assurance of student learning, and continuous improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a 2009 study by Nicholson and DeMoss indicated ''a perceived deficiency in the degree of integration of ethics and social responsibility into various specific disciplines.'' Several authors have extolled the effectiveness of an integrated approach to teaching business ethics whereby in addition to stand-alone courses, ethics is taught throughout the business curriculum (Willey et al 2012;Cant and Kulik 2009;Wilhelm 2010).…”
Section: Why Educating For Caring Design Can Workmentioning
confidence: 99%